Differential expression of Ago2‐mediated microRNA signaling in adipose tissue is associated with food‐induced obesity. Issue 10 (5th September 2022) - Zhang, Hansi; Qiao, Liang; Liu, Xiaoxuan; Han, Xiaojing; Kang, Jing; Liu, Yanli; Lin, Juntang; Yan, Xin
Abstract : Adipose tissue is a major component for the regulation of energy homeostasis by storage and release of lipids. As a core element of RNA‐induced silencing complex, argonaute2 (Ago2) plays critical role in maintenance of systemic metabolic demand. Here, we show that high‐fat‐diet‐fed mice exhibit an increase in body mass alongside systematic insulin resistance and altered rate of energy expenditure. Interestingly, Ago2 expression is associated with obesity and an increased amount of adipose tissue. Moreover, increased levels of Ago2 inhibited the expression of AMPKα by promoting its targeting by miR‐148a, the most abundant microRNA in adipose tissues. Those results suggested that Ago2– miR‐148a – AMPKα signaling pathway play an important function in the developing obesity and adiposity, and will further provide basic research data for the potential clinical treatment of obesity. Abstract : Here, we show that Ago2 expression is increased in adipose tissue of mice with food‐induced obesity. An increase in Ago2 promotes the expression of microRNA‐148a and subsequently inhibits the expression of its target AMPKα, a regulator of insulin sensitivity and energy homeostasis in adipose tissue. This study identifies that the Ago2‐miR‐148a signaling pathway plays a key role in the progression of diet‐induced obesity.